Lactic Acid Bacteria Strains Exert Immunostimulatory Effect on H. pylori-Induced Dendritic Cells. (22nd February 2015) - Wiese, Małgorzata; Eljaszewicz, Andrzej; Helmin-Basa, Anna; Andryszczyk, Marek; Motyl, Ilona; Wieczyńska, Jolanta; Gackowska, Lidia; Kubiszewska, Izabela; Januszewska, Milena; Michałkiewicz, Jacek
Abstract : The aim of this study was to find out if selected lactic acid bacteria (LAB) strains (antagonistic or nonantagonistic against H. pylori in vitro ) would differ in their abilities to modulate the DCs maturation profiles reflected by their phenotype and cytokine expression patterns. Methods . Monocyte-derived DCs maturation was elicited by their direct exposure to the LAB strains of L. rhamnosus 900 or L. paracasei 915 (antagonistic and nonantagonistic to H. pylori, resp.), in the presence or absence of H. pylori strain cagA+ . The DCs maturation profile was assessed on the basis of surface markers expression and cytokines production. Results . We observed that the LAB strains and the mixtures of LAB with H. pylori are able to induce mature DCs. At the same time, the L. paracasei 915 leads to high IL-10/IL-12p70 cytokine ratio, in contrast to L. rhamnosus 900. Conclusions . This study showed that the analyzed lactobacilli strains are more potent stimulators of DC maturation than H. pylori . Interestingly from the two chosen LAB strains the antagonistic to H. pylori-L. rhamnosus strain 900 has more proinflammatory and probably antibactericidal properties.